Associations Between Telomere Length and Hearing Status in Mid-Childhood and Midlife: Population-Based Cross-Sectional study. Issue 5 (September 2019) - Wang, Jing; Nguyen, Minh Thien; Sung, Valerie; Grobler, Anneke; Burgner, David; Saffery, Richard; Wake, Melissa
Abstract : Objectives: The purpose of this study is to determine if telomere length (a biomarker of aging) is associated with hearing acuity in mid-childhood and midlife. Design: The study was based on the population-based cross-sectional study within the Longitudinal Study of Australian Children with telomere length and audiometry data. We calculated high Fletcher Index (hFI, mean threshold of 1, 2, and 4 kHz), defining hearing loss as threshold >15 dB HL (better ear). Linear and logistic regression analyses quantified associations of telomere length with continuous hearing threshold and binary hearing loss outcomes, respectively. Results: One thousand one hundred ninety-five children (mean age 11.4 years, SD 0.5) and 1334 parents (mean age 43.9 years, SD 5.1) were included in analyses. Mean (SD) telomere length (T/S ratio) was 1.09 (0.55) for children and 0.81 (0.38) for adults; hFI (dB HL) was 8.0 (5.6) for children and 13.1 (7.0) for adults, with 8.4% and 25.9%, respectively, showing hearing loss.Telomere length was not associated with hearing threshold or hearing loss in children (hFI: OR, 0.99; 95% confidence interval, 0.55 to 1.78) or adults (hFI: OR, 1.35; 95% confidence interval, 0.81 to 2.25). Conclusions: Telomere length was not associated with hearing acuity in children or their midlife parents. Abstract : Supplemental Digital Content is available in the text.